Is it worth it to personalize the treatment of PTSD? – A variance-ratio meta-analysis and estimation of treatment effect heterogeneity in RCTs of PTSD. (October 2022) - Herzog, Philipp; Kaiser, Tim
Abstract: Several evidence-based treatments for posttraumatic stress disorder (PTSD) are recommended by international guidelines (e.g., APA, NICE). While their average effects are in general high, non-response rates indicate differential treatment effects. Here, we used a large database of RCTs on psychotherapy for PTSD to determine a reliable estimate of this heterogeneity in treatment effects (HTE) by applying Bayesian variance ratio meta-analysis. In total, 66 studies with a total of 8803 patients were included in our study. HTE was found for all psychological treatments, with varying degrees of certainty, only slight differences between psychological treatments, and active control groups yielding a smaller variance ratio compared to waiting list control groups. Across all psychological treatment and control group types, the estimate for the intercept was 0.12, indicating a 12% higher variance of posttreatment values in the intervention groups after controlling for differences in treatment outcomes. This study is the first to determine the maximum increase in treatment effects of psychological treatments for PTSD by personalization. The results indicate that there is comparatively high heterogeneity in treatment effects across all psychological treatment and control groups, which in turn allow personalizing psychological treatments by using treatment selection approaches. Highlights: Non-response rates of psychological treatments for PTSD indicate differential treatment effects. Using a database of RCTs on psychotherapy for PTSD, we empirically estimated this heterogeneity of treatment effects (HTE). We found comparatively high HTE across all treatments and control groups with only slight differences between treatments. Active control groups yielded a smaller HTE compared to waiting list control groups. Data-driven personalization of psychotherapy for PTSD by treatment selection is a promising future research avenue.